Contribution to the knowledge of the aphaenopsian genus Sinaphaenops Uéno et Wang, 1991 (Coleoptera: Carabidae: Trechini) - Chen, Jujian; Tang, Mingruo; Yang, Pingjing; Tian, Mingyi (Zootaxa, 2017)
A revision of the genus Sinaphaenops Uéno et Wang, 1991 is provided, with a modified key to species. Two new species are described and illustrated in southern Guizhou Province: S. yaolinensis sp. n. (from a limestone cave called Yaolin Rongdong, Du’yun Shi) and S. banshanicus sp. n. (from Cave Banshan Dong, Guiding County). Male genital characteristics of S. mochongensis Tian et Huang, 2014 are reported for the first time. New records for other three Sinaphaenops species are given. In addition, an identification key to subgenera and species of Sinaphaenops is provided.